What competencies should early childhood educators possess for the future? An expert judgement approach - Pinya-Medina, Carme; Morcillo-Loro, Virginia; Ferrer-Ribot, María; Oliver Barceló, María del Mar (Frontiers in Education, 2024)
Introduction The objective of this research was to identify and discuss the professional competencies essential for early childhood educators to effectively navigate current challenges and anticipate future ones. The study aims to contribute to the development of a competency framework tailored specifically for early childhood education. Methods A proposed set of general teaching competencies was subjected to validation by a panel of experts, including early childhood teachers and academic professionals specializing in this field. The process involved adapting and refining these competencies to suit the early childhood education stage. Results Expert consultation confirmed the relevance and appropriateness of the proposed competency dimensions for early childhood educators. The experts emphasized several critical aspects, including the importance of building relationships, providing emotional support, employing nonverbal communication, and fostering family involvement. They also highlighted the significance of observation and educational documentation in the early years. Discussion The findings underscore the need for reflection on the specific professional competencies required for early childhood educators, which is crucial for enhancing both initial and ongoing teacher training programs. This research contributes to the ongoing dialogue about the competencies necessary for educators, emphasizing the development of teaching practices that address the unique demands of early childhood education.